Exploring Brand Hate and the Association Between Similar Competitor Offer and Brand Equity: A Moderated-Mediation Model - Husnain, Mudassir; Wang, Zanxin; Poulova, Petra; Syed, Fauzia; Akbar, Ahsan; Akhtar, Muhammad Waheed; Akbar, Minhas; Usman, Muhammad (Frontiers in Psychology, 2021)
Using the assumptions of Sternberg (2003) Duplex Theory of Hate, the present study reveals the combined effects of similar competitor offer and narcissistic personality on brand equity through the underlying mechanism of brand hate. Specifically, we hypothesize that brand hate mediates the relationship between similar competitor offer and brand equity. Moreover, we propose that similar competitor offer and brand hate relationship are stronger for narcissistic individuals. By employing a multi-wave time-lagged research design, we collected data from a sample of (N = 338) dairy product consumers in Pakistan. The findings of moderated-mediation regression analyses indicate that (a) Brand hate mediates the relationship between similar competitor offer and brand equity; and (b) Narcissistic personality moderates a similar competitor offer and brand hate relationship such that a high similar competitor offer led to greater brand hate when narcissism was high. Furthermore, conditional indirect effects reveal that brand hate mediates the relationship between similar competitor offer and brand equity only with individuals exhibiting narcissistic personality traits. The current study offers great insights to managers that by managing similar competitor offer, they can manage the development of brand hate, which can subsequently effect brand equity. Moreover, by profiling customers on the basis of their personalities, marketing managers can effectively invest only in customers with positive tendencies. The current study is unique in that it highlights new avenues in existing research by extending the nascent domain of brand hate in consumer–brand relationships.